2021
DOI: 10.2147/ijn.s319348
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Spanlastics for Improving the Ocular Delivery of Clotrimazole: In vitro Characterization, Ex vivo Permeability, Microbiological Assessment and In vivo Safety Study

Abstract: Purpose The aim of this study was to encapsulate clotrimazole (CLT), an antifungal drug with poor water solubility characteristics, into spanlastics (SPs) to provide a controlled ocular delivery of the drug. Methods Span 60 was used in the formulation of SPs with Tween 80, Pluronic F127, or Kolliphor RH40 as an edge activator (EA). The presence of EA offers more elasticity to the membrane of the vesicles which is expected to increase the corneal permeation of CLT. SPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…So, Tween ® 80 was more hydrophobic than Pluronic F127, therefore, Tween ® 80-based NSPs were more rigid by decreasing the amphiphilic property of the vesicles’ membrane, resulting in higher EE% [ 31 ]. These results are in agreement with those of Abdelbari et al [ 32 ] who reported higher EE% with Tween ® 80-based splanlastics than Pluronic F127-based NSPs for the ocular delivery of clotrimazole.…”
Section: Resultssupporting
confidence: 93%
“…So, Tween ® 80 was more hydrophobic than Pluronic F127, therefore, Tween ® 80-based NSPs were more rigid by decreasing the amphiphilic property of the vesicles’ membrane, resulting in higher EE% [ 31 ]. These results are in agreement with those of Abdelbari et al [ 32 ] who reported higher EE% with Tween ® 80-based splanlastics than Pluronic F127-based NSPs for the ocular delivery of clotrimazole.…”
Section: Resultssupporting
confidence: 93%
“…The microplate photometer (Tecan Sunrise absorbance reader, Reading, UK) was employed to calculate any color change caused by XTT decrease at 492 nm. The following is the equation used to determine inhibition % (Abdelbari et al., 2021 ): …”
Section: Methodsmentioning
confidence: 99%
“…Hydrophobicity of stearic acid arises from its long alkyl chain (C18) along with its saturation reflecting in high phase transition temperature (Tc = 69 °C), leading to the formation of less leaky vesicles resulting in higher EE%. Regarding factor B ( p < 0.0001), increasing ratio or concentration of span 80 having low HLB (4.3) (Ruckmani & Sankar, 2010 ) due to its long alkyl chain of oleate moiety(C18) (Abdelbary et al, 2017 ), resulting in less hydrophilic holes and reducing the fluidity of the membrane by reducing the bilayers amphiphilic property (Abdelbari et al, 2021 ). Moreover, it was found that the EE% value increases upon increasing surfactant concentration which could be attributed to the added emulsification and stabilization impact of the lipid material in the presence of high surfactant concentration (Abdelbary & Fahmy, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cholesterol intercalates inside the bilayer by placing the polar head toward the hydrophilic surface and the aliphatic chain parallel to the surfactant alkyl chains, accordingly PS increased (Emad Eldeeb et al, 2019 ). Also, the presence of a large amount of vesicles-forming materials relative to the hydration medium would lead to accumulation of multiple layers over each other and thus PS increased (Abdelbari et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%